2020
DOI: 10.1016/j.jagp.2020.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Liability for Depression, Social Factors and Their Interaction Effect in Depressive Symptoms and Depression Over Time in Older Adults

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…To account for population structure, PCs were calculated on genetic data prior to imputation. In the replication cohort, cases were genotyped on the GSA array and the controls on the Axiom-NL array from Affymetrix (Avera Institute for Human Genetics, Sioux Falls, SD) [ 26 , 27 ]. Quality control was performed in the same way as described for the discovery dataset for cases and controls independently and frequencies of the variants were compared after imputation.…”
Section: Methodsmentioning
confidence: 99%
“…To account for population structure, PCs were calculated on genetic data prior to imputation. In the replication cohort, cases were genotyped on the GSA array and the controls on the Axiom-NL array from Affymetrix (Avera Institute for Human Genetics, Sioux Falls, SD) [ 26 , 27 ]. Quality control was performed in the same way as described for the discovery dataset for cases and controls independently and frequencies of the variants were compared after imputation.…”
Section: Methodsmentioning
confidence: 99%
“…Another study showed with increase in the subject age, greater depressive symptoms were present (Rippon & Steptoe, 2018). Other factors mentioned concerning older age depression were genetic, brain anatomical, and cytokine levels (Derry et al, 2021;Klinedinst et al, 2015;Laird et al, 2019;Stringa et al, 2020;Wang et al, 2018).…”
Section: Biological Factorsmentioning
confidence: 95%
“…;Horita et al, 2013;Jovanova et al, 2016;Karczewska & Młynarska, 2021;Leggett et al, 2012;Meesters et al, 2014;Nicolosi et al, 2011; Olsen, Schirmer, Wilsgaard, Bønaa, & Hanssen, 2018;Popescu et al, 2012;Pusswald et al, 2012; Rhee, Jang, Kim, & Chang, 2021;Rzewuska et al, 2015;Sadler, McLaren, & Jenkins, 2013; Sanders, Comijs, Bremmer, Deeg, & Beekman, 2015;Wang et al, 2016; Ylli et al, 2016), older age(Olsen et al, 2018;Rippon & Steptoe, 2018;Rzewuska et al, 2015), genetics(Klinedinst, Resnick, Yerges-Armstrong, & Dorsey, 2015;Stringa et al, 2020), brain anatomical(Laird et al, 2019;Wang et al, 2018), cytokine level(Derry et al, 2021), taking drugs(Bond et al, 2020), low activity(Davison, McCabe, Knight, & Mellor, 2012; Kobyla nska et al, 2019; …”
mentioning
confidence: 99%
“…Suppose y i is a binary outcome; this is, of course, a common analytic scenario (Ancelin et al, 2017;Culverhouse et al, 2018;Stringa et al, 2020). We will discuss this scenario in the context of Figure 1.…”
Section: Binary Outcomesmentioning
confidence: 99%